INFLUENCE OF CURRENT TRANSFORMER ERRORS ON THE CALCULATOR INDICATOR - Egamov Dilmurod Abduraimovich; Erkinov Shodibek Rasuljon ugli (Лучшие интеллектуальные исследования, 2024)
Abstract: This article describes the principle of operation of the current transformer, the factors that cause measurement errors, the connection diagram, the formula for determining the error that occurred during the operation of the current transformer, and the ways to eliminate the error that occurred.